Pursuing Social Justice in Educational Robotics - Manolis Wallace; Vassilis Poulopoulos (MDPI AG, 2022)
In educational systems that make their first attempt to incorporate STEAM concepts in their teaching, educational robotics is typically the place to start; robotics kits are purchased, and a small group of pupils is typically selected to develop a project and perhaps to also take part in some local or national robotics competition. Whilst this can be a very stimulating and rewarding experience for the participating pupils, it does little to introduce STEAM to the rest of the pupils in the school. In this article, we present our work towards a more fair and socially just approach to educational robotics. Compared with the conventional approach to educational robotics, our work introduces the following novelties: (A) shorter educational programs so that equipment can be re-used, (B) out-of-school implementation so that the programs are accessible to pupils from all schools, even from those schools that do not have teachers willing to be involved in STEAM programs and (C) scaling via the training of teachers who then act as multipliers of our action. The approach was applied, before being interrupted by the COVID-19 pandemic, in a specially developed innovation hub, and the initial results are reported herein. Based on those findings, the potential of our approach to achieve a broader societal impact is highlighted.